1890 Ky. Acts 618, An Actsto Establish a City Government for the Town of North Middle-Town, ch 327 Article III §7. - (:unkn) unknown (General Publisher, 1890)
The council should have the power tor regulate and restrain the firing and concealed carry of firearms.
--
Keywords: DISCHARGE